Effect of Threshold Inspiratory Muscle Training on Functional Fitness and Respiratory Muscle Strength Compared to Incentive Spirometry in Children and Adolescents With Obesity: A Randomized Controlled Trial - Kaeotawee, Phatthareeda; Udomittipong, Kanokporn; Nimmannit, Akarin; Tovichien, Prakarn; Palamit, Apinya; Charoensitisup, Pawinee; Mahoran, Khunphon (Frontiers in Pediatrics, 2022)
Background: To determine the effect of threshold inspiratory muscle training (IMT) on functional fitness and respiratory muscle strength compared to incentive spirometry (IS) in children/adolescents with obesity. Methods: A total of 60 obese children/adolescents aged 8-15 years were randomized into the threshold IMT group (n=20), the IS group (n=20), or the control group (n=20). The IMT group performed 30 inspiratory breaths with the intensity set at 40% of baseline maximal inspiratory pressure (MIP) twice daily for 8 weeks; the IS group performed 30 breaths with sustained maximum inspiration twice daily for 8 weeks; and, the control group was assigned no training device for 8 weeks. Six-minute walk test (6-MWT), respiratory muscle strength, and spirometry were compared between baseline and 8 weeks. Results: Six-MWT distance (528.5±36.2 vs. 561.5±35.2 meters, p=0.002) and MIP (121.2±26.8 vs. 135.3±32.1%Predicted, p=0.03) were significantly improved after 8 weeks of IMT training. There was no significant difference in any evaluated pulmonary function parameters between baseline and 8 weeks in the IS or control groups; however, 6-MWT distance demonstrated a trend towards significant improvement in the IS group (526.9±59.1vs.549.0±50.6 meters, p=0.10). No significant difference among groups was found for any variable relative to change from baseline to post-training. Conclusions: Eight weeks of threshold IMT training significantly improved both inspiratory muscle strength (MIP) and functional fitness (6-MWT) in children/adolescents with obesity. Eight weeks of IS training yielded a trend towards significantly improved functional fitness.